Clinical Characteristics of Liver Cirrhosis Patients in Internal Medicine Inpatient Ward of Fatmawati General Hospital and Factors Affecting Mortality during Hospitalization - Nikko Darnindro; Annela Manurung; Edi Mulyana; Arnold Manurung (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: liver cirrhosis is a global health problem. The mortality rate due to cirrhosis was estimated to achieve 1 million per year worldwide. The aim of this study is to elaborate the characteristics of patients  with liver cirrhosis and factors affecting mortality during hospitalization in Fatmawati General Hospital.Method: The design of this study was retrospective cohort involving patients admitted to the hospital between January and March 2019.Results: Among 41 liver cirrhosis patients, it was found that the average age was 52.9 ±13.8 years old and the percentage of male patients among participants was 75.6%. Patients who died during hospitalization was 12.2%. The average length of stay in hospital was 10.8±6.4 days. Patients were admitted to the hospital with various complaints; the most common complaint was gastrointestinal bleeding in 46.3%, decreased consciousness in 22% and massive ascites in 17.1% patients. Physical examination findings of anaemic conjunctiva, icteric sclera, and shifting dullness were found in 73.2%; 29.3% and 61% patients, respectively. Icteric condition during hospital admission has higher mortality risk with RR 9.6 (95% CI: 1.2-77.8). Approximately 53.7% cirrhosis patients were diagnosed with hepatitis B, while 22% of them  were diagnosed with hepatitis C. Coinfection of hepatitis B and C were found in 4.8% patients, while 29% patients were neither infected with hepatitis B nor C. Based on the laboratory examination, creatinine level 1.3 mg/dL had higher mortality risk with RR 8.3 (95% CI: 1.04-66.7), while natrium level ≤ 125 mmol/L had higher mortality risk with RR 26.4 (95% CI: 3.6-191). Based on Child-Pugh classification, 24.4% patients had Child-Pugh A, while 14.6% had Child Pugh C, and 39% patients could not be classified. The mean Child-Pugh score in this study was 8 ± 2.2. Through the bivariate analysis, we found the association between Child-Pugh classification and mortality; higher classification has higher mortality risk (p = 0.028). Child-Pugh C had mortality risk with RR = 9.5 (95% CI: 1.2-75.1).Conclusion: Liver cirrhosis patients were hospitalized due to the ongoing decompensation. The mortality rate during hospitalization in liver cirrhosis patients was high. Mortality in these patients was associated with icteric condition upon admission, high initial creatinine level, low sodium level, and high Child-Pugh classification.